Descriptions of three new Brazilian Subrasaca species, redescription of S. nigriventris (Signoret, 1855) and a key to males of the genus (Hemiptera: Cicadellidae: Cicadellini) - Da Silva, Roberta Dos Santos; Cavichioli, Rodney Ramiro; Mejdalani, Gabriel (Zootaxa, 2013)
Three new species of the Neotropical sharpshooter genus Subrasaca Young, 1977 from Southeastern and Southern Brazil are described and illustrated: S. diminuta sp. nov. (State of São Paulo and State of Paraná), S. rubra sp. nov. (State of Minas Gerais and State of São Paulo), and S. rachelae sp. nov. (State of Espírito Santo). Subrasaca nigriventris (Signoret, 1855) is reinterpreted, redescribed and illustrated based on specimens from Southeastern Brazil (State of Rio de Janeiro). In addition to the external morphology, color pattern, and male genitalia, this paper includes detailed descriptions and illustrations of the female genitalia. A key to males of all known Subrasaca species is provided.